Lithium iron phosphate positive plate, preparation method thereof and lithium ion battery
By using stacked lithium iron phosphate nanosheets and coated carbon layers in lithium iron phosphate positive electrode sheets, the problem of low rate performance of lithium iron phosphate positive electrode sheets is solved, and higher charge transfer efficiency and lower production costs are achieved.
Patent Information
- Application Number
- CN202510019254.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-06
AI Technical Summary
The current lithium iron phosphate positive electrode sheet has low rate performance, resulting in higher charge transfer impedance and ion diffusion impedance during charge and discharge.
By using stacked lithium iron phosphate nanosheets and a carbon layer coated on the surface of lithium iron phosphate nanosheets in the lithium iron phosphate positive electrode sheet, the lithium iron phosphate nanosheets are stacked with (010) surface as the stacking surface, and the carbon bond connection between the carbon layer and the current collector is improved to improve the conductivity and interaction force of the positive electrode active layer.
This technology effectively shortens the diffusion path of lithium ions, reduces charge transfer impedance and ion diffusion impedance, improves the rate performance and cycle stability of lithium iron phosphate positive electrode sheets, and reduces production costs.
Smart Images

Figure CN119890233A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a lithium iron phosphate positive electrode sheet and a preparation method thereof, and a lithium ion battery. Background Art
[0002] As one of the most promising new energy sources, lithium-ion batteries are the preferred energy source for electric and hybrid vehicles. Among them, lithium iron phosphate (LiFePO4) materials have been widely used in power batteries due to their low raw material cost, stable structure, and high safety. LiFePO4 has a typical olivine structure, a high theoretical capacity (170mAh / g), sufficient operating voltage (3.45Vvs.Li + / Li) and long cycle life (greater than 2000 cycles). However, lithium iron phosphate has an obvious shortcoming, namely the slow diffusion rate of lithium ions, which leads to poor electrochemical performance. Inside the LiFePO4 lattice, lithium ions diffuse along the channel in the b-axis direction, that is, the
[010] direction, and are deintercalated at the interface where the LiFePO4 and FePO4 crystal structures coexist. From this point of view, since the LiFePO4 crystal structure is anisotropic, regulating the selectivity of the (010) surface of the LiFePO4 crystal structure can effectively promote lithium ion diffusion and thus improve the rate performance of LiFePO4.
[0003] However, regulating the preference of the (010) plane of the LiFePO4 crystal structure means that the material has strong anisotropy and is mostly in the form of flakes or plates. It is difficult to ensure the orientation of lithium iron phosphate materials in the same direction during the slurry mixing and coating process, which will not only lead to poor processing performance of the electrode in the coating process, i.e. low compaction and rough surface, but also cause the lithium iron phosphate nanomaterials in the finished product to be distributed in random directions. The high anisotropy increases the path of ion diffusion, resulting in poor actual rate performance. Therefore, it is urgent to develop a lithium iron phosphate electrode sheet that can ensure both high compaction and high rate performance. Summary of the invention
[0004] The main purpose of the present invention is to provide a lithium iron phosphate positive electrode sheet and a preparation method thereof and a lithium ion battery, so as to solve the problem of low rate performance of lithium iron phosphate positive electrode sheets in the prior art.
[0005] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, a lithium iron phosphate positive electrode sheet is provided, comprising a current collector and a positive electrode active layer located on the surface thereof, wherein the surface of the current collector contains carbon, and the material of the positive electrode active layer comprises stacked lithium iron phosphate nanosheets and a carbon layer coated on the surface of the lithium iron phosphate nanosheets, wherein the lithium iron phosphate nanosheets have the (010) plane as the stacking plane.
[0006] The diffusion of lithium ions in lithium iron phosphate is mainly along the
[010] direction. The lithium iron phosphate nanosheets in the lithium iron phosphate positive electrode sheet of the present application are stacked on the current collector along the (010) plane, which helps to increase the charge transfer area of the lithium iron phosphate positive electrode sheet during the charging and discharging process, shorten the diffusion path of lithium ions, and reduce the charge transfer impedance and ion diffusion impedance of the lithium iron phosphate reaction, thereby helping to improve the rate performance of the lithium iron phosphate positive electrode sheet. The presence of the carbon layer in the lithium iron phosphate positive electrode sheet helps to improve the conductivity and stability of the positive electrode active layer on the one hand; on the other hand, the carbon layer and the current collector are connected by carbon bonds, which helps to improve the interaction between the positive electrode active layer and the current collector.
[0007] Furthermore, the average plane diameter of the lithium iron phosphate nanosheets is 100nm~300nm, and the average thickness is 10nm~30nm.
[0008] The lithium iron phosphate nanosheets having an average plane diameter within the above range are helpful to provide more lithium ion reaction sites, thereby helping to increase the lithium ion deintercalation rate. The lithium iron phosphate nanosheets having a thickness within the above range are helpful to shorten the diffusion path of lithium ions within the material, thereby facilitating the improvement of the rate performance of the lithium iron phosphate positive electrode sheet.
[0009] Furthermore, the mass ratio of the lithium iron phosphate nanosheets to the carbon layer is 1:0.012-0.070; and / or the current collector is carbon paper and / or carbon fiber cloth.
[0010] Controlling the mass ratio of lithium iron phosphate nanosheets to carbon layers within the above range helps to improve the cycle stability and rate performance of the positive electrode active layer.
[0011] According to another aspect of the present invention, a method for preparing the aforementioned lithium iron phosphate positive electrode sheet is provided, and the preparation method comprises: step S1, mixing raw materials including a lithium source, an iron source, a phosphorus source, a reducing agent, water and a surfactant to obtain a mixed solution; step S2, heat-treating a current collector in an oxygen-containing gas to obtain a heat-treated current collector; step S3, placing the heat-treated current collector and the mixed solution in a reactor for hydrothermal reaction to obtain a current collector loaded with lithium iron phosphate nanosheets, wherein the current collector is placed flat on the bottom of the reactor; step S4, calcining the current collector loaded with lithium iron phosphate nanosheets in a protective gas to obtain a lithium iron phosphate positive electrode sheet.
[0012] The role of the reducing agent is to reduce ferric iron to ferrous iron, and the role of the surfactant is to regulate the morphology and growth direction of lithium iron phosphate to form (010) face stacked lithium iron phosphate nanosheets, and the surfactant also serves as a carbon source, and a carbon layer can be formed on the surface of the lithium iron phosphate nanosheets after subsequent calcination. In step S2, the current collector is heat-treated in an oxygen-containing gas, which helps to increase the number of oxygen-containing functional groups on the surface of the current collector, thereby helping to improve the adsorption capacity of the surfactant on the surface of the lithium iron phosphate nanosheets. In step S3, the heat-treated current collector and the mixed solution are placed in a reactor for hydrothermal reaction to obtain a current collector loaded with lithium iron phosphate nanosheets. The current collector loaded with lithium iron phosphate nanosheets is calcined to convert the surfactant into a carbon layer, and the carbon layer and the current collector are connected by carbon bonds, which helps to improve the interaction between the current collector and the positive electrode active layer and improve the crystallinity of the lithium iron phosphate nanosheets.
[0013] Furthermore, in the above step S3, the temperature of the hydrothermal reaction is 150-300° C.; and / or the time of the hydrothermal reaction is 6-10 hours.
[0014] Controlling the temperature and time of the hydrothermal reaction within the above range helps to improve the purity and morphology consistency of lithium iron phosphate.
[0015] Furthermore, in the above step S4, the heating rate of calcination is 0.5-10°C / min; and / or the calcination temperature is 600-850°C; and / or the calcination holding time is 2-6h.
[0016] Controlling the heating rate, temperature and holding time of calcination within the above ranges helps to improve the crystallinity of lithium iron phosphate and the efficiency of converting the surfactant into a carbon layer.
[0017] Furthermore, in the above step S2, the heat treatment temperature is 400-500°C; and / or, the heat treatment time is 2-6 hours; and / or, the volume content of oxygen in the oxygen-containing gas is not less than 21%.
[0018] Controlling the temperature and time of the heat treatment within the above ranges helps to enhance the interaction between the surfactant and the current collector.
[0019] Furthermore, in the above step S1, the volume ratio of water to the reducing agent is 1-2:3; and / or, the molar ratio of the lithium element in the lithium source, the iron element in the iron source and the phosphorus element in the phosphorus source is (0.9-1.1): (0.9-1.1): (0.9-1.1); and / or, the mass proportion of water in the raw material is 20%-40%; and / or, the mass of the surfactant accounts for 2%-10% of the total mass of the lithium source, the iron source and the phosphorus source; and / or, the reducing agent is ethylene glycol and / or ethanol; and / or, the surfactant is selected from polyvinyl alcohol, polyvinyl pyrrolidone any one or more of ketone and sodium dodecylbenzene sulfonate; preferably, the surfactant is polyvinyl alcohol, and the number average molecular weight of the polyvinyl alcohol is 170000-220000 g / mol; and / or, the lithium source is selected from any one or more of lithium carbonate, lithium nitrate, lithium acetate, lithium hydroxide and lithium sulfate; and / or, the iron source is selected from any one or more of ferrous chloride, ferrous sulfate, ferrous oxalate, ferrous acetate, ferric nitrate and ferrous dihydrogen phosphate; and / or, the phosphorus source is selected from any one or more of phosphoric acid, ferrous dihydrogen phosphate, ammonium dihydrogen phosphate and diammonium hydrogen phosphate.
[0020] Controlling the volume ratio of water to the reducing agent within the above range helps to improve the formation efficiency of lithium iron phosphate nanosheets. Preferably, the molar ratio of the lithium element in the lithium source, the iron element in the iron source, and the phosphorus element in the phosphorus source is controlled within the above range, which helps to reduce the generation of impurities. Preferably, the mass proportion of water in the raw material is controlled within the above range, which helps to control the viscosity of the reaction system, thereby helping to improve the formation efficiency of lithium iron phosphate nanosheets. Preferably, the mass of the surfactant is controlled to account for the total mass of the lithium source, iron source, and phosphorus source within the above range, which helps to control the mass ratio of the lithium iron phosphate nanosheet to the carbon layer within a suitable range, thereby helping to improve the rate performance and cycle stability of the lithium iron phosphate positive electrode sheet.
[0021] Furthermore, the above step S3 also includes washing and drying the product after the hydrothermal reaction in sequence to obtain a current collector loaded with lithium iron phosphate nanosheets; preferably, the drying is carried out in a vacuum drying oven; and / or the drying temperature is 60~100°C; and / or the drying time is 3~6h.
[0022] Washing and drying the products after the hydrothermal reaction in sequence can help further reduce the content of impurities in the lithium iron phosphate nanosheets.
[0023] According to another aspect of the present invention, a lithium-ion battery is provided, comprising a positive electrode sheet, an electrolyte and a negative electrode sheet, wherein the positive electrode sheet is the aforementioned lithium iron phosphate positive electrode sheet.
[0024] The above lithium-ion battery has a high rate performance.
[0025] By applying the technical solution of the present invention, the existence of lithium iron phosphate in the form of nanosheets helps to shorten the diffusion path of lithium ions inside the material, thereby helping to reduce the charge transfer impedance and ion diffusion impedance, and further helping to improve the rate performance of the lithium iron phosphate positive electrode sheet. The diffusion of lithium ions in lithium iron phosphate is mainly along the
[010] direction. In the lithium iron phosphate positive electrode sheet of the present application, the lithium iron phosphate nanosheets are stacked on the current collector along the (010) plane, which helps to increase the charge transfer area of the lithium iron phosphate positive electrode sheet during the charging and discharging process, shorten the diffusion path of lithium ions, reduce the charge transfer impedance and ion diffusion impedance of the lithium iron phosphate reaction, and further help to improve the rate performance of the lithium iron phosphate positive electrode sheet. The presence of the carbon layer in the lithium iron phosphate positive electrode sheet helps to improve the conductivity and stability of the positive electrode active layer on the one hand; on the other hand, the carbon layer and the current collector are connected by carbon bonds, which helps to improve the interaction between the positive electrode active layer and the current collector. Traditional lithium iron phosphate positive electrode sheets contain binders and conductive agents, while the lithium iron phosphate positive electrode sheets of the present application do not contain binders and conductive agents, and there is no need to prepare the positive electrode material into a slurry for coating, and there is no problem of difficult coating process. Therefore, the production cost of the lithium iron phosphate positive electrode sheets of the present application is relatively low. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0027] Figure 1 The charge and discharge curve of the lithium iron phosphate positive electrode sheet at a rate of 0.2C in Example 1 of the present application is shown;
[0028] Figure 2 The cycle performance diagram of the lithium iron phosphate positive electrode sheet in Example 1 of the present application at the rates of 0.2C, 0.5C, 1C, and 2C is shown;
[0029] Figure 3 The SEM image of the cross section of the lithium iron phosphate positive electrode in Example 1 of the present application is shown. DETAILED DESCRIPTION
[0030] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0031] As analyzed in the background technology of this application, the prior art has the problem of low rate performance of lithium iron phosphate positive electrode sheets. In order to solve the above problem, this application provides a lithium iron phosphate positive electrode sheet, a preparation method thereof, and a lithium ion battery.
[0032] In a typical embodiment of the present application, a lithium iron phosphate positive electrode sheet is provided, including a current collector and a positive electrode active layer located on the surface thereof, the surface of the current collector contains carbon, the material of the positive electrode active layer includes stacked lithium iron phosphate nanosheets and a carbon layer coated on the surface of the lithium iron phosphate nanosheets, and the lithium iron phosphate nanosheets have the (010) plane as the stacking plane.
[0033] The presence of lithium iron phosphate in the form of nanosheets helps to shorten the diffusion path of lithium ions inside the material, thereby helping to reduce the charge transfer impedance and ion diffusion impedance, and further helping to improve the rate performance of the lithium iron phosphate positive electrode sheet. The diffusion of lithium ions in lithium iron phosphate is mainly along the
[010] direction. In the lithium iron phosphate positive electrode sheet of the present application, the lithium iron phosphate nanosheets are stacked on the current collector along the (010) plane, which helps to increase the charge transfer area of the lithium iron phosphate positive electrode sheet during the charge and discharge process, shorten the diffusion path of lithium ions, and reduce the charge transfer impedance and ion diffusion impedance of the lithium iron phosphate reaction, thereby helping to improve the rate performance of the lithium iron phosphate positive electrode sheet. The presence of the carbon layer in the lithium iron phosphate positive electrode sheet helps to improve the conductivity and stability of the positive electrode active layer on the one hand; on the other hand, the carbon layer and the current collector are connected by carbon bonds, which helps to improve the interaction between the positive electrode active layer and the current collector. Traditional lithium iron phosphate positive electrode sheets contain binders and conductive agents, while the lithium iron phosphate positive electrode sheets of the present application do not contain binders and conductive agents, and there is no need to prepare the positive electrode material into a slurry for coating, and there is no problem of difficult coating process. Therefore, the production cost of the lithium iron phosphate positive electrode sheets of the present application is relatively low.
[0034] In one embodiment of the present application, the average plane diameter of the lithium iron phosphate nanosheets is 100 nm to 300 nm, and the average thickness is 10 nm to 30 nm.
[0035] Preferably, the average plane diameter of the lithium iron phosphate nanosheet is controlled within the above range, which helps to provide more lithium ion reaction sites, thereby helping to increase the rate of lithium ion deintercalation, and further helping to increase the specific capacity of the lithium iron phosphate positive electrode sheet. At the same time, the nanosheets within the above size range help to maintain good interlayer contact when stacked, thereby facilitating uniform distribution and rapid transmission of charge. Preferably, the thickness of the lithium iron phosphate nanosheet is controlled within the above range, which helps to shorten the diffusion path of lithium ions inside the material, thereby facilitating improving the rate performance of the lithium iron phosphate positive electrode sheet.
[0036] In one embodiment of the present application, the mass ratio of the lithium iron phosphate nanosheets to the carbon layer is 1:0.012-0.070; and / or the current collector is carbon paper and / or carbon fiber cloth.
[0037] Too little carbon layer content is not conducive to improving the conductivity and structural stability of the positive electrode active layer. Too much carbon layer content is not conducive to improving the specific capacity and energy density of the lithium iron phosphate positive electrode sheet. It is preferred to control the mass ratio of lithium iron phosphate nanosheets to carbon layer within the above range, which helps to improve the cycle stability and rate performance of the positive electrode active layer.
[0038] In another typical embodiment of the present application, a method for preparing the aforementioned lithium iron phosphate positive electrode sheet is provided, and the preparation method comprises: step S1, mixing raw materials including a lithium source, an iron source, a phosphorus source, a reducing agent, water and a surfactant to obtain a mixed solution; step S2, heat-treating a current collector in an oxygen-containing gas to obtain a heat-treated current collector; step S3, placing the heat-treated current collector and the mixed solution in a reactor for hydrothermal reaction to obtain a current collector loaded with lithium iron phosphate nanosheets, wherein the current collector is placed flat on the bottom of the reactor; step S4, calcining the current collector loaded with lithium iron phosphate nanosheets in a protective gas to obtain a lithium iron phosphate positive electrode sheet.
[0039] In step S1, raw materials including a lithium source, an iron source, a phosphorus source, a reducing agent, water and a surfactant are mixed to obtain a mixed solution. The role of the reducing agent is to reduce trivalent iron to divalent iron, the role of the surfactant is to regulate the morphology and growth direction of lithium iron phosphate to form (010) face stacked lithium iron phosphate nanosheets, and the surfactant also serves as a carbon source, and a carbon layer can be formed on the surface of the lithium iron phosphate nanosheets after subsequent calcination. The presence of the carbon layer helps to improve the conductivity and stability of the positive electrode active layer on the one hand; on the other hand, the carbon layer and the current collector are connected by carbon bonds, which helps to improve the interaction between the positive electrode active layer and the current collector. In step S2, the current collector is heat-treated in an oxygen-containing gas, which helps to increase the number of oxygen-containing functional groups on the surface of the current collector, thereby helping to improve the adsorption capacity of the surfactant on the surface of the lithium iron phosphate nanosheet. In step S3, the heat-treated current collector and the mixed solution are placed in a reactor for hydrothermal reaction to obtain a current collector loaded with lithium iron phosphate nanosheets. The current collector loaded with lithium iron phosphate nanosheets is calcined to convert the surfactant into a carbon layer. The carbon layer and the current collector are connected by carbon bonds, which helps to improve the interaction between the current collector and the positive electrode active layer and improve the crystallinity of the lithium iron phosphate nanosheets.
[0040] Including but not limited to, the above-mentioned protective gas is selected from any one or more of argon, nitrogen and helium.
[0041] In one embodiment of the present application, the above-mentioned step S1 includes: step S11, adding a lithium source, an iron source and a phosphorus source to a mixed solution of a certain amount of water and a reducing agent, stirring and dissolving, to obtain a mixed solution A; step S12, heating and dissolving a surfactant in water at 70~90°C to prepare a surfactant aqueous solution, adding it to the mixed solution A and stirring evenly to obtain a mixed solution B; and using the mixed solution B as a mixed solution.
[0042] In one embodiment of the present application, in the above step S3, the temperature of the hydrothermal reaction is 150-300° C.; and / or the time of the hydrothermal reaction is 6-10 hours.
[0043] Insufficient temperature or time of the hydrothermal reaction is not conducive to reducing the content of impurities in lithium iron phosphate. During the hydrothermal reaction, the precursor gradually forms lithium iron phosphate nanosheets under the induction of the surfactant. Under the mutual attraction between the current collector and the surfactant, the lithium iron phosphate nanosheets coated with the surfactant are gradually stacked on the carbon paper. It is preferred to control the temperature and time of the hydrothermal reaction within the above range, which helps to improve the purity of lithium iron phosphate and the consistency of morphology.
[0044] In one embodiment of the present application, in the above step S4, the heating rate of calcination is 0.5-10°C / min; and / or the calcination temperature is 600-850°C; and / or the calcination holding time is 2-6h.
[0045] If the calcination temperature is too low or the holding time is too short, it is not conducive to improving the crystallinity of the lithium iron phosphate nanosheets. If the calcination temperature is too high or the holding time is too long, it is not conducive to reducing the content of impurities such as iron phosphide and lithium phosphate. It is preferred to control the heating rate, temperature and holding time of the calcination within the above range, which is helpful to improve the crystallinity of the lithium iron phosphate and improve the efficiency of converting the surfactant into the carbon layer.
[0046] In order to enhance the interaction force between the surfactant and the current collector, in one embodiment of the present application, preferably, in the above step S2, the heat treatment temperature is 400-500°C; and / or, the heat treatment time is 2-6h; and / or, the volume content of oxygen in the oxygen-containing gas is not less than 21%.
[0047] In one embodiment of the present application, in the above step S1, the volume ratio of water to the reducing agent is 1~2:3; and / or, the molar ratio of the lithium element in the lithium source, the iron element in the iron source and the phosphorus element in the phosphorus source is (0.9~1.1): (0.9~1.1): (0.9~1.1); and / or, the mass proportion of water in the raw material is 20%~40%; and / or, the mass of the surfactant accounts for 2%~10% of the total mass of the lithium source, the iron source and the phosphorus source; and / or, the reducing agent is ethylene glycol and / or ethanol; and / or, the surfactant is selected from polyvinyl alcohol, polyethylene Any one or more of pyrrolidone and sodium dodecylbenzene sulfonate; preferably, the surfactant is polyvinyl alcohol, and the number average molecular weight of the polyvinyl alcohol is 170000-220000 g / mol; and / or, the lithium source is selected from any one or more of lithium carbonate, lithium nitrate, lithium acetate, lithium hydroxide and lithium sulfate; and / or, the iron source is selected from any one or more of ferrous chloride, ferrous sulfate, ferrous oxalate, ferrous acetate, ferric nitrate and ferrous dihydrogen phosphate; and / or, the phosphorus source is selected from any one or more of phosphoric acid, ferrous dihydrogen phosphate, ammonium dihydrogen phosphate and diammonium hydrogen phosphate.
[0048] Too high or too low a content of the reducing agent is not conducive to the formation of nanosheets of lithium iron phosphate. It is preferred to control the volume ratio of water to the reducing agent within the above range, which helps to improve the formation efficiency of lithium iron phosphate nanosheets. Preferably, the reducing agent is ethylene glycol, which has a higher viscosity, which helps to slow down the diffusion of substances and thus inhibit nucleation growth. It is preferred to control the molar ratio of the lithium element in the lithium source, the iron element in the iron source, and the phosphorus element in the phosphorus source within the above range, which helps to reduce the generation of impurities. It is preferred to control the mass ratio of water in the raw material within the above range, which helps to control the viscosity of the reaction system, thereby helping to improve the formation efficiency of lithium iron phosphate nanosheets. The surfactant is adsorbed on the (010) surface during the reaction to inhibit the vertical growth of lithium iron phosphate, thereby inducing the production of lithium iron phosphate nanosheets with a (010) surface. During the calcination process, the surfactant will be converted into an inorganic carbon layer and evenly coated on the lithium iron phosphate nanosheet. If the surfactant content is too low, it is not conducive to improving the uniformity of the carbon layer coating, and thus is not conducive to improving the conductivity of the positive electrode active layer; if the surfactant content is too high, it is not conducive to improving the specific capacity of the material. It is preferred to control the mass of the surfactant to the total mass of the lithium source, iron source and phosphorus source within the above range, which helps to control the mass ratio of the lithium iron phosphate nanosheet to the carbon layer within a suitable range, thereby helping to improve the rate performance and cycle stability of the lithium iron phosphate positive electrode sheet. Preferably, the surfactant is polyvinyl alcohol, and the number average molecular weight of the polyvinyl alcohol is controlled within the above range, which helps to produce more lithium iron phosphate nanosheets with (010) faces, thereby helping to improve the rate performance of the lithium iron phosphate positive electrode sheet. It is preferred to control the types of lithium source, iron source and phosphorus source within the above range, which helps to improve the mutual synergy between the components, thereby helping to further improve the rate performance of the lithium iron phosphate positive electrode sheet.
[0049] In order to further reduce the content of impurities in the lithium iron phosphate nanosheets, thereby improving the rate performance of the lithium iron phosphate positive electrode sheet, in one embodiment of the present application, preferably, the above-mentioned step S3 also includes washing and drying the product after the hydrothermal reaction in sequence to obtain a current collector loaded with lithium iron phosphate nanosheets, preferably drying in a vacuum drying oven; and / or, the drying temperature is 60~100°C; and / or, the drying time is 3~6h.
[0050] In another typical embodiment of the present application, a lithium-ion battery is provided, including a positive electrode sheet, an electrolyte and a negative electrode sheet, wherein the positive electrode sheet is the aforementioned lithium iron phosphate positive electrode sheet.
[0051] Since the lithium ion battery contains the lithium iron phosphate positive electrode sheet of the present application, the lithium ion battery has a higher rate performance.
[0052] The beneficial effects of the present application will be further illustrated below in conjunction with embodiments.
[0053] Example 1
[0054] (1) adding lithium hydroxide, ferrous chloride and ammonium dihydrogen phosphate into a mixed solution of water and ethylene glycol at a molar ratio of Li:Fe:P of 1:1:1, stirring and dissolving to obtain solution A;
[0055] (2) heating polyvinyl alcohol to dissolve in water to prepare a polyvinyl alcohol aqueous solution, adding the solution to solution A, and stirring evenly to obtain solution B, wherein the polyvinyl alcohol accounts for 5% of the total mass of lithium hydroxide, ferrous chloride and ammonium dihydrogen phosphate, and the number average molecular weight of the polyvinyl alcohol is 170000 g / mol; the mass proportion of water in solution B is 40%, and the volume ratio of water to ethylene glycol is 2:3;
[0056] (3) heat treating the carbon paper at 500° C. for 2 hours in an air atmosphere to obtain heat-treated carbon paper;
[0057] (4) The heat-treated carbon paper and solution B are transferred into a sealed reactor for hydrothermal reaction, wherein the carbon paper is placed at the bottom of the inner lining of the reactor and reacted at 200°C for 8 hours.
[0058] (5) After cooling, collect the carbon paper with lithium iron phosphate nanosheets loaded on the bottom, wash it with deionized water, and then put it into a vacuum drying oven for drying. The temperature of the vacuum drying oven is set to 70°C and the drying time is 4 hours.
[0059] (6) The dried carbon paper loaded with lithium iron phosphate nanosheets was placed in a nitrogen atmosphere and calcined at 650°C for 4 h at a heating rate of 5°C / min to obtain a lithium iron phosphate positive electrode sheet. The mass ratio of the lithium iron phosphate nanosheets to the carbon layer in the lithium iron phosphate positive electrode sheet was 1:0.03, the average planar diameter of the lithium iron phosphate nanosheets was 154 nm, and the average thickness was 19 nm.
[0060] Example 2
[0061] The difference from Example 1 is that the temperature of the hydrothermal reaction is 150° C., the time of the hydrothermal reaction is 10 h, and finally a lithium iron phosphate positive electrode sheet is obtained.
[0062] Example 3
[0063] The difference from Example 1 is that the temperature of the hydrothermal reaction is 300° C., the time of the hydrothermal reaction is 6 hours, and finally a lithium iron phosphate positive electrode sheet is obtained.
[0064] Example 4
[0065] The difference from Example 1 is that the temperature of the hydrothermal reaction is 350° C., the time of the hydrothermal reaction is 5 h, and finally a lithium iron phosphate positive electrode sheet is obtained.
[0066] Example 5
[0067] The difference from Example 1 is that the calcination heating rate is 0.5°C / min, the calcination temperature is 850°C, the calcination holding time is 2h, and finally a lithium iron phosphate positive electrode sheet is obtained, wherein the average plane diameter of the lithium iron phosphate nanosheets is 253nm and the average thickness is 27nm.
[0068] Example 6
[0069] The difference from Example 1 is that the calcination heating rate is 10°C / min, the calcination temperature is 600°C, the calcination holding time is 6h, and finally a lithium iron phosphate positive electrode sheet is obtained, wherein the average plane diameter of the lithium iron phosphate nanosheets is 121nm and the average thickness is 13nm.
[0070] Example 7
[0071] The difference from Example 1 is that the calcination heating rate is 15°C / min, the calcination temperature is 900°C, the calcination holding time is 1h, and finally a lithium iron phosphate positive electrode sheet is obtained, wherein the average plane diameter of the lithium iron phosphate nanosheets is 306nm and the average thickness is 32nm.
[0072] Example 8
[0073] The difference from Example 1 is that the number average molecular weight of polyvinyl alcohol is 220,000 g / mol, and a lithium iron phosphate positive electrode sheet is finally obtained.
[0074] Example 9
[0075] The difference from Example 1 is that the number average molecular weight of polyvinyl alcohol is 350,000 g / mol, and a lithium iron phosphate positive electrode sheet is finally obtained.
[0076] Example 10
[0077] The difference from Example 1 is that polyvinyl alcohol accounts for 10% of the total mass of lithium hydroxide, ferrous chloride and ammonium dihydrogen phosphate, and a lithium iron phosphate positive electrode sheet is finally obtained. The mass ratio of lithium iron phosphate nanosheets to carbon layers in the lithium iron phosphate positive electrode sheet is 1:0.07.
[0078] Embodiment 11
[0079] The difference from Example 1 is that polyvinyl alcohol accounts for 15% of the total mass of lithium hydroxide, ferrous chloride and ammonium dihydrogen phosphate, and a lithium iron phosphate positive electrode sheet is finally obtained. The mass ratio of lithium iron phosphate nanosheets to carbon layers in the lithium iron phosphate positive electrode sheet is 1:0.10.
[0080] Example 12
[0081] The difference from Example 1 is that (1) lithium nitrate, ferrous oxalate and diammonium hydrogen phosphate are added to a mixed solution of water and ethylene glycol at a molar ratio of Li:Fe:P of 1.1:0.9:1.1, and stirred to dissolve to obtain solution A;
[0082] (2) heating polyvinyl alcohol to dissolve in water to prepare a polyvinyl alcohol aqueous solution, adding the solution to solution A, and stirring evenly to obtain solution B, wherein the polyvinyl alcohol accounts for 5% of the total mass of lithium nitrate, ferrous oxalate and diammonium hydrogen phosphate, and the number average molecular weight of the polyvinyl alcohol is 170000 g / mol; the mass proportion of water in solution B is 20%, and the volume ratio of water to ethylene glycol is 1:3;
[0083] (3) heat treating the carbon paper at 500° C. for 2 hours in an air atmosphere to obtain heat-treated carbon paper;
[0084] (4) The heat-treated carbon paper and solution B are transferred into a sealed reactor for hydrothermal reaction, wherein the carbon paper is placed at the bottom of the inner lining of the reactor and reacted at 200°C for 8 hours.
[0085] (5) After cooling, collect the carbon paper with lithium iron phosphate nanosheets loaded on the bottom, wash it with deionized water, and then put it into a vacuum drying oven for drying. The temperature of the vacuum drying oven is set to 60°C and the drying time is 6 hours;
[0086] (6) The dried carbon paper loaded with lithium iron phosphate nanosheets was placed in a nitrogen atmosphere and calcined at 650°C for 4 h at a heating rate of 5°C / min to obtain a lithium iron phosphate positive electrode sheet.
[0087] Example 13
[0088] The difference from Example 1 is that (1) lithium carbonate, ferrous oxalate and phosphoric acid are added to a mixed solution of water and ethylene glycol at a molar ratio of Li:Fe:P of 0.9:1.1:0.9, and stirred to dissolve to obtain solution A;
[0089] (2) heating polyvinyl alcohol to dissolve in water to prepare a polyvinyl alcohol aqueous solution, adding the solution to solution A, and stirring evenly to obtain solution B, wherein the polyvinyl alcohol accounts for 2% of the total mass of lithium carbonate, ferrous oxalate and phosphoric acid, and the number average molecular weight of the polyvinyl alcohol is 170000 g / mol; the mass proportion of water in solution B is 40%, and the volume ratio of water to ethylene glycol is 2:3;
[0090] (3) heat treating the carbon paper at 500° C. for 2 hours in an air atmosphere to obtain heat-treated carbon paper;
[0091] (4) The heat-treated carbon paper and solution B are transferred into a sealed reactor for hydrothermal reaction, wherein the carbon paper is placed at the bottom of the inner lining of the reactor and reacted at 200°C for 8 hours.
[0092] (5) After cooling, collect the carbon paper with lithium iron phosphate nanosheets loaded on the bottom, wash it with deionized water, and then put it into a vacuum drying oven for drying. The temperature of the vacuum drying oven is set to 100°C and the drying time is 3 hours;
[0093] (6) The dried carbon paper loaded with lithium iron phosphate nanosheets was placed in a nitrogen atmosphere and calcined at 650°C for 4 h at a heating rate of 5°C / min to obtain a lithium iron phosphate positive electrode sheet.
[0094] Comparative Example 1
[0095] The difference from Example 1 is that carbon paper is not added in step (4). Finally, the positive electrode material is prepared by first dissolving polyvinylidene fluoride (PVDF) in N-methylpyrrolidone solvent (NMP), wherein the mass ratio of polyvinylidene fluoride (PVDF) is 5%. The positive electrode material, polyvinylidene fluoride (PVDF), and carbon black SuperP are mixed in a mass ratio of 8:1:1 to obtain a slurry coated on the surface of the carbon layer paper, and placed in an oven for drying to obtain a lithium iron phosphate positive electrode sheet.
[0096] Comparative Example 2
[0097] The difference from Example 1 is that polyvinyl alcohol is not added in step (2), and carbon paper is not added in step (4). Finally, the positive electrode material is prepared by first dissolving polyvinylidene fluoride (PVDF) in N-methylpyrrolidone solvent (NMP), wherein the mass ratio of polyvinylidene fluoride (PVDF) is 5%. The positive electrode material, polyvinylidene fluoride (PVDF), and carbon black SuperP are mixed in a mass ratio of 8:1:1 to obtain a slurry coated on the surface of carbon paper, and placed in an oven for drying to obtain a lithium iron phosphate positive electrode sheet.
[0098] Performance Testing
[0099] The lithium iron phosphate positive electrode sheet and lithium sheet prepared in the embodiment and comparative example were used as the counter electrode and reference electrode, and 1 mol / L lithium hexafluorophosphate electrolyte were assembled into button cells. The assembled button cells were subjected to constant current charge and discharge tests at rates of 0.2C, 0.5C, 1C, and 2C, and the first discharge specific capacity at different rates was recorded. The charge and discharge window was set to 2.5V~4.0V. The test results are shown in Table 1.
[0100] Table 1
[0101]
[0102] Figure 1 The charge and discharge curve of the lithium iron phosphate positive electrode sheet at a rate of 0.2C in Example 1 of the present application is shown in FIG. Figure 1 It can be seen that there is a flat charging and discharging platform, no side reactions are observed, and the polarization of the reaction is small.
[0103] Figure 2 The cycle performance diagram of the lithium iron phosphate positive electrode sheet at the rates of 0.2C, 0.5C, 1C, and 2C in Example 1 of the present application. The lithium iron phosphate positive electrode sheet is subjected to three charge and discharge cycles at the rates of 0.2C, 0.5C, 1C, and 2C in sequence. Figure 2 It can be calculated that the average discharge mass specific capacity at 0.2C is 158.2mAh / g, the average discharge mass specific capacity at 0.5C is 152.4mAh / g, the average discharge mass specific capacity at 1C is 145.5mAh / g, and the average discharge mass specific capacity at 2C is 135.1mAh / g, showing good rate performance.
[0104] Figure 3 This is a SEM image of the cross section of the lithium iron phosphate positive electrode in Example 1 of the present application, Figure 3 It can be seen that the lithium iron phosphate nanosheets grow with the (010) plane as the preferred plane.
[0105] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:
[0106] The presence of lithium iron phosphate in the form of nanosheets helps to shorten the diffusion path of lithium ions inside the material, thereby helping to reduce the charge transfer impedance and ion diffusion impedance, and further helping to improve the rate performance of the lithium iron phosphate positive electrode sheet. The diffusion of lithium ions in lithium iron phosphate is mainly along the
[010] direction. In the lithium iron phosphate positive electrode sheet of the present application, the lithium iron phosphate nanosheets are stacked on the current collector along the (010) plane, which helps to increase the charge transfer area of the lithium iron phosphate positive electrode sheet during the charge and discharge process, shorten the diffusion path of lithium ions, and reduce the charge transfer impedance and ion diffusion impedance of the lithium iron phosphate reaction, thereby helping to improve the rate performance of the lithium iron phosphate positive electrode sheet. The presence of the carbon layer in the lithium iron phosphate positive electrode sheet helps to improve the conductivity and stability of the positive electrode active layer on the one hand; on the other hand, the carbon layer and the current collector are connected by carbon bonds, which helps to improve the interaction between the positive electrode active layer and the current collector. Traditional lithium iron phosphate positive electrode sheets contain binders and conductive agents, while the lithium iron phosphate positive electrode sheets of the present application do not contain binders and conductive agents, and there is no need to prepare the positive electrode material into a slurry for coating, and there is no problem of difficult coating process. Therefore, the production cost of the lithium iron phosphate positive electrode sheets of the present application is relatively low.
[0107] The above are only embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A lithium iron phosphate positive electrode sheet, comprising a current collector and a positive electrode active layer located on the surface thereof, characterized in that: The surface of the current collector contains carbon, and the material of the positive electrode active layer includes stacked lithium iron phosphate nanosheets and a carbon layer coated on the surface of the lithium iron phosphate nanosheets, and the lithium iron phosphate nanosheets have a (010) plane as a stacking plane.
2. The lithium iron phosphate positive electrode sheet according to claim 1, characterized in that: The average plane diameter of the lithium iron phosphate nanosheets is 100nm-300nm, and the average thickness is 10nm-30nm.
3. The lithium iron phosphate positive electrode sheet according to claim 1 or 2, characterized in that: The mass ratio of the lithium iron phosphate nanosheets to the carbon layer is 1:0.012-0.070; and / or the current collector is carbon paper and / or carbon fiber cloth.
4. A method for preparing a lithium iron phosphate positive electrode sheet according to any one of claims 1 to 3, characterized in that: The preparation method comprises: Step S1, mixing raw materials including a lithium source, an iron source, a phosphorus source, a reducing agent, water and a surfactant to obtain a mixed solution; Step S2, heat-treating the current collector in an oxygen-containing gas to obtain a heat-treated current collector; Step S3, placing the heat-treated current collector and the mixed solution in a reactor for hydrothermal reaction to obtain a current collector loaded with lithium iron phosphate nanosheets, wherein the current collector is placed flat on the bottom of the reactor; Step S4, calcining the current collector loaded with lithium iron phosphate nanosheets in a protective gas to obtain the lithium iron phosphate positive electrode sheet.
5. The preparation method according to claim 4, characterized in that: In step S3, the temperature of the hydrothermal reaction is 150-300° C.; and / or the time of the hydrothermal reaction is 6-10 hours.
6. The preparation method according to claim 4 or 5, characterized in that: In the step S4, the heating rate of the calcination is 0.5-10°C / min; and / or the calcination temperature is 600-850°C; and / or the calcination holding time is 2-6h.
7. The preparation method according to any one of claims 4 to 6, characterized in that: In step S2, the heat treatment temperature is 400-500° C.; and / or, the heat treatment time is 2-6 hours; and / or, the volume content of oxygen in the oxygen-containing gas is not less than 21%.
8. The preparation method according to any one of claims 4 to 7, characterized in that In the step S1, the volume ratio of the water to the reducing agent is 1-2:3; And / or, the molar ratio of the lithium element in the lithium source, the iron element in the iron source and the phosphorus element in the phosphorus source is (0.9-1.1):(0.9-1.1):(0.9-1.1); And / or, the mass proportion of water in the raw material is 20% to 40%; And / or, the mass of the surfactant accounts for 2% to 10% of the total mass of the lithium source, the iron source and the phosphorus source; And / or, the reducing agent is ethylene glycol and / or ethanol; And / or, the surfactant is selected from any one or more of polyvinyl alcohol, polyvinyl pyrrolidone and sodium dodecylbenzene sulfonate; preferably, the surfactant is polyvinyl alcohol, and the number average molecular weight of the polyvinyl alcohol is 170000-220000 g / mol; And / or, the lithium source is selected from any one or more of lithium carbonate, lithium nitrate, lithium acetate, lithium hydroxide and lithium sulfate; And / or, the iron source is selected from any one or more of ferrous chloride, ferrous sulfate, ferrous oxalate, ferrous acetate, ferric nitrate, and ferrous dihydrogen phosphate; And / or, the phosphorus source is selected from any one or more of phosphoric acid, ferrous dihydrogen phosphate, ammonium dihydrogen phosphate and diammonium hydrogen phosphate.
9. The preparation method according to any one of claims 4 to 8, characterized in that: The step S3 also includes washing and drying the product after the hydrothermal reaction in sequence to obtain the current collector loaded with lithium iron phosphate nanosheets; preferably, the drying is carried out in a vacuum drying oven; and / or, the drying temperature is 60~100°C; and / or, the drying time is 3~6h.
10. A lithium ion battery comprising a positive electrode, an electrolyte and a negative electrode, characterized in that: The positive electrode sheet is the lithium iron phosphate positive electrode sheet according to any one of claims 1 to 3.
Citation Information
Patent Citations
Lithium iron phosphate positive electrode material, preparation method and lithium ion battery
CN115863576A
Method for manufacturing iron phosphate lithium
JP2012180239A
Method for manufacturing an olivine-type silicate compound including a transition metal
JP2014118329A
Positive electrode for lithium-sulfur battery, methodof preparing same, and lithium-sulfur batterycomprising same
KR1020040013585A
Power storage device and method for manufacturing the same
US20110065004A1
Cited By
Lithium iron phosphate positive electrode material, positive electrode sheet and preparation method thereof
CN120565640A
Lithium iron phosphate cathode material, cathode sheet and its preparation method
CN120565640B